Extended-spectrum beta-lactamases producing extensively drug-resistant Salmonella Typhi in Punjab, Pakistan - Muhammad Saeed; Muhammad Hidayat Rasool; Farhan Rasheed; Muhammad Saqalein; Muhammad Atif Nisar; Ambreen Anwar Imran; Saba Tariq; Afreenish Amir; Aamer Ikram; Mohsin Khurshid (Journal of Infection in Developing Countries)
Introduction: The multidrug-resistant (MDR) Salmonella enterica serovar Typhi isolates have been increasingly reported from the Asian and African countries. The emergence of isolates with decreased susceptibility to fluoroquinolones and cephalosporins has worsened the situation. Recently, an outbreak from Sindh, Pakistan was reported caused by extensively drug-resistant (XDR) S. Typhi strains.